MENELISIK KINERJA GOVERNANCE DI DAERAH OTONOMI KHUSUS PAPUA BARAT - Ivan Giddeon Fanggidae; Hidayatul fajri; Pandhu Yuanjaya (Yogyakarta State University, 2016)
The implementation of special autonomy in West Papua province aims to increase the development. Centralized development has brought the people of West Papua in a slump multidimensional. The purpose of this article describes the governance performance that the implementation of special autonomy in failure. This article used a qualitative approach. Source of data used comes from RKPD West Papua Province, Public Welfare Indicators (BPS), IGI (parnership), and TKED (The Asia Foundation). The main findings in this article was not prosperous West Papua still has even though the special autonomy fund and the exploitation of natural high. The main indicators are still at the education and welfare of the lowest rankings in Indonesia. Performance Governance and the worst is in the government bureaucracy. This led to the existing resources can not be the welfare of society as stalled in bureaucracy and government.Keywords: Special Autonomy Funds, Governance Performance, and West Papua